Association of aquatic biota with mangrove plants in the land transfer area of Lino Tolongano Village, South Banawa District, Donggala Regency and as a media for public information - Syech Zainal; Aan Febriawan; Moh. Sabran (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Mangrove forest is a unique natural ecosystem with high ecological value. The mangrove ecosystem is one of the areas with high productivity due to the presence of litter and litter decomposition occurs and produces detritus. This study aims to describe aquatic biota associated with the remaining stands of mangrove plants in the area of land conversion in Lino Tolonggano Village, South Banawa District, Donggala Regency, so that the surrounding community can be informed about the importance of the existence of mangrove forests. This type of research is descriptive quantitative research, with survey method with purposive sampling technique. The data obtained were analyzed using the association determination formula as well as additional posters that will be used as information material to the public regarding the existence of mangroves in the area of land conversion. The results obtained in this study indicate that the types of mangroves and associated aquatic biota are Sonneratia alba, Rhizophora mucronata and Rhizophora apiculata for the mangrove group and Nerita sp, Telescopium telescopium L, Uca sp and Periophthalmus modestus for the aquatic biota group. Data analysis showed that there were associations between plant species in the form of negative associations. This indicates that the aquatic biota found are not biota that use mangroves as a place to live.